From Archives of Lost Architecture to AR. Canonica’s Farmhouses from the XIX Century to the Present Day - Cecilia Maria Bolognesi; Deida Bassorizzi (img journal)
The tangible and intangible traces of our heritage are the means for reconstructing the image of our history; in the context of today's technological advancement VR and AR are pivotal tools for reconstructing and narrating this reality. The pervasiveness of 3D reconstruction, however, requires reflection: how do we validate the products of these techniques within a broader scientific society, and how do we consider reconstructions of our heritage appropriate? In the case study here presented we will deal with the reconstructions of some rural complexes in the Park of Monza that no longer exist because they were demolished in the last century; these rural buildings had been built with specific functions to support the park and the life of the royal palace, which had lost their reason to exist when the productive life of the court had ceased. However, the hand that had built them had left several realizations that have come down to us, making the digital reconstruction with a strong hypothesis of verisimilitude.